(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
An assignment problem (AP) is a particular case of a transportation problem, in which the objective is to assign a number of facilities to an equal number of activities at an overall minimum cost, distance, time (or maximum profit). It occupies extremely a major part in the real physical world. The most common method used to solve the APs is the Hungarian method. In this paper, we make an endeavor to introduce a new ones assignment approach namely MASS (Modified Assignment) for finding optimal pattern of assignments to a wide range of APs. 2010 Mathematics Subject Classification: 90C08, 90C10